THE EFFECT OF BOILING TIME VARIATIONS ON THE CHARACTERISTICS OF MILLET SEED SNACK BARS (PANICUM MILIACEUM) - Widyastuti, Retno; Asmoro, Novian Wely; Febrianti, Anisya (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Millet seeds are one of the sources of carbohydrates that have the potential to be used as an alternative to non-rice food. However, information on its processing is still limited, another weakness is that millet seeds are difficult to grind because the skin sticks tightly. There needs to be innovation in processing, including making snack bars. Snack bars are one of the solid food preparations that have complete nutritional content and are made from a combination of several food ingredients with the help of binders. In this study, snack bars were made using millet seeds as raw materials with chocolate as a binder. This study aims to determine the effect of the length of time for boiling millet seeds on the chemical and physical characteristics of snack bar products. This study used a completely randomized design with one factor, namely the length of time for boiling millet seeds (50 minutes, 60 minutes, 70 minutes). The data obtained were analyzed using One Way Anova analysis and to determine whether there was a difference in treatment, the Duncan Multiple Range Test (DMRT) was continued with a significance of 5%. The results of the experiment showed that the snackbar product had chemical characteristics including water content of 2.53-9.53%, ash content of 1.52-1.19%, protein content of 6.69-7.25%, fat content of 21.54-28.21%, carbohydrate content of 57.58-61.23 and the level of hardness (texture) obtained was 27.86-45.55 N.